Faculty verbal messages: scale development and initial validation - Violanti, Michelle T.; Garland, Michelle E. (Frontiers in Education, 2024)
This study set out to develop and initially validate a Faculty Verbal Messages scale. During focus groups, an initial list of 65 faculty messages was generated; exploratory factor analysis reduced the number of messages to 34. A third study sought to validate the 34 messages and examine whether the scale performed as expected in conjunction with relational motives, relational distance, learner empowerment, and student motivation. Results indicated the number of faculty verbal messages could be further reduced to 19; messages mediated the motives to communicate-learner empowerment relationship and indirectly predicted student motivation.